The Role of Paralegals in the Child Protection System in Villages: A Study of Timor Tengah Utara Regency - Yohanes Fritantus; Hendrikus H Botha (Asosiasi Peneliti dan Pengajar Ilmu Sosial Indonesia, 2024)
The 1945 Constitution, Article 28B paragraph (2), and the regulations under it, such as Laws and Ministerial Regulations, have detailed provisions regarding the child protection system. The method in this research is qualitative research, with data collection techniques including observation, documentation, and interviews. The research results indicate that since the enactment of the Regional Regulation of North Central Timor Regency Number 15 of 2016, the Regent's Regulation of North Central Timor Number 54 of 2017, and the Regent's Regulation of North Central Timor Number 55 of 2017, the North Central Timor Regency government, through the Women's and Children's Empowerment Office, has established paralegals in the villages. In carrying out their duties, paralegals formally receive a Decree from the Regent and from the Village Government. Paralegals serve as the extended arm of the local government in providing outreach at the village level and assisting child and female victims in both litigation and non-litigation resolutions.